The effect of vitamin C on fibroblast proliferation and VEGFexpression in fibroblast culture - Yohanes Widodo Wirohadidjojo, Munira, Sunardi Radiono (Universitas Gadjah Mada, 2009)
Background: One of the factors that determine the success of efficient woul)d healing is wound healing rate, that can be achieved by increasingcell proliferation, angiogenesisor neovascularisation,and extracellular matrix production. Dermalfibroblast is a cell that plays an important role in wound healing. Fibroblast proliferation and neovascularisation are critical elements in granular tissue formation. Local hypoxia causes fibroblasts to express HIF-1a that will induce fibroblast VEGFexpression. The nature of vitamin C makes it easily oxidized. The addition of vitamin Con fibroblast culture medium is expected to produce local hypoxia condition that will induce fibroblast expression of HIF-1a, so that the expression of fibroblast VEGFwill be increased. Vitamin C may modulate the growth of various types of cells. The effect of vitamin Con normal fibroblast proliferation and fibroblast VEGFexpression is still unknown. Objective: This study was aimed to know whether vitamin Ccan increase normal human fibroblast proliferation and expression of VEGF. Method: A simple experimental study was conducted by using preputial skin fibroblast culture from 10-year-old donor, subculture passage 3. Fibroblast culture was divided into 6 groups, each group received vitamin C treatment with the dose of 50pg/mL, 100pg/mL, 150pg/mL, 200pg/mL, and 300pg/mL, and one group without treatment acting as control. Measurement of fibroblast proliferation was conducted by spectrophotometer using MTT, and fibroblast expression of VEGFwas measured using ELISA. The average of difference in fibroblast proliferation and VEGFexpression was analyzed with one-way analysis of variance. Result: There was a significant increase in fibroblast proliferation rate in the groups receiving vitamin C with the dose of 200 mg/mL (p = 0.016) and 300 mg/mL (p = 0.005), whereas in the group with the dose of 50 mg/mL, 100 mg/mL and 150 mg/mL there was no significant difference compared to the control (p = 0.933, p = 0.961, P = 0.301, respectively). Average fibroblast VEGFexpression between various concentrations of vitamin C compared to the control showed no significant difference (p > 0.05). Conclusion: Vitamin Ccould be considered to be used as an agent to accelerate wounds healing. Keywords: vitamin C, skin fibroblast culture, fibroblast proliferation, fibroblast VEGFexpression